Computer-simulated TOUCH prosthesis cup malposition and solutions - Knappe, Kevin; Schonhoff, Mareike; Jäger, Sebastian; Bickert, Berthold; Harhaus-Wähner, Leila; Panzram, Benjamin (Hand surgery & rehabilitation, 2024)
Introduction - Total joint replacement has become significantly more common as a treatment for advanced trapeziometacarpal joint osteoarthritis in recent years. The latest generation of prostheses with dual-mobility designs leads to very good functional results and low rates of loosening and dislocation in the short and medium term. Biomechanical studies showed that central placement and parallel alignment of the cup with respect to the proximal articular surface of the trapezium are crucial for both cup stability and prevention of dislocation. Despite correct positioning of the guidewire, incorrect placement or tilting of the inserted cup may occur, requiring immediate intraoperative revision. - Methods - The existing spherical and conical cup models in sizes 9 mm and 10 mm were transferred to a computer-aided design dataset. Depending on the intraoperative complication (tilting or incorrect placement), the revision options resulting from the various combinations of cup type and size were simulated and analyzed according to the resulting defect area and bony contact area. - Results - In well centered cups, a size 9 conical cup could be replaced by a size 9 spherical cup and still be fixed by press-fit. Conversely, a size 9 spherical cup could not be replaced by a size 9 conical cup, but only by a size 10 cup, of whatever shape. When a size 9 conical cup was tilted up to 20°, the best revision option was to resect the sclerotic margin and insert a size 10 conical cup deeper into the cancellous bone, to achieve the largest contact area with the surrounding bone. When a size 9 cup of whatever shape was poorly centered (misplaced with respect to the dorsopalmar or radioulnar line of the trapezium), placement should be corrected using a size 10 cup, combined with autologous bone grafting of the defect. Again, the size 10 conical cup showed the largest bony contact area. - Conclusion - Our computer-based measurements suggested options for intraoperative cup revision depending on cup shape and size and on type of misalignment with resulting bone defects. These suggestions, however, need to be confirmed in anatomic specimens before introducing them into clinical practice.